2021
DOI: 10.1016/j.xjtc.2021.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular assist device–promoted recovery and technical aspects of explant

Abstract: Feature Editor Note-Promoting left ventricular recovery after durable left ventricular assist device (LVAD) implantation remains a Holy Grail. Currently, less than 2% of patients exhibit signs of recovery after LVAD implantation, and even fewer tolerate device explantation without recurrence of heart failure. In this issue of the Journal, Drs Faerber and Doenst describe what we can do clinically to promote recovery, including how guidelinedirected medical therapy may facilitate structural remodeling of the unl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Thus, there should be no hesitation about a longer waiting time with VAD support if patient safety can be guaranteed. In addition to factors associated with VAD-promoted myocardial recovery in adults [ 23 ], age <2 years at VAD implantation, with a myocarditis diagnosis, and less myocardial fibrosis are thought to be predictors for recovery of left ventricular function during VAD support in children [ 14 , 24 ]. However, the specific factors that promoted late recovery in this study have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there should be no hesitation about a longer waiting time with VAD support if patient safety can be guaranteed. In addition to factors associated with VAD-promoted myocardial recovery in adults [ 23 ], age <2 years at VAD implantation, with a myocarditis diagnosis, and less myocardial fibrosis are thought to be predictors for recovery of left ventricular function during VAD support in children [ 14 , 24 ]. However, the specific factors that promoted late recovery in this study have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Faerber and colleagues 1 provide an expert review of the current state of using durable LVADs to promote myocardial recovery and achieve long-term freedom from heart failure. Faerber and colleagues 1 discuss a number of important conceptual and practical issues currently surrounding the use of durable LVADs to promote myocardial recovery.…”
mentioning
confidence: 99%
“…Faerber and colleagues 1 provide an expert review of the current state of using durable LVADs to promote myocardial recovery and achieve long-term freedom from heart failure. Faerber and colleagues 1 discuss a number of important conceptual and practical issues currently surrounding the use of durable LVADs to promote myocardial recovery. First, although numerous studies have demonstrated improvement in the biology of the recovered heart associated with mechanical unloading, improvement in biology alone is insufficient to predict the degree of functional recovery or long-term freedom from heart failure.…”
mentioning
confidence: 99%
“…The authors have put together a thorough document. 1 The road to myocardial recovery will be paved with a fundamental understanding of biology, innovative research on potential therapeutics, and the utility of chronic mechanical unloading.…”
mentioning
confidence: 99%